The Epigenetic Landscape of Vascular Calcification: An Integrative Perspective - Hou, Yi-Chou; Lu, Chien-Lin; Yuan, Tzu-Hang; Liao, Min-Tser; Chao, Chia-Ter; Lu, Kuo-Cheng (International journal of molecular sciences, 2020)
Vascular calcification (VC) is an important complication among patients of advanced age, those with chronic kidney disease, and those with diabetes mellitus. The pathophysiology of VC encompasses passive occurrence of physico-chemical calcium deposition, active cellular secretion of osteoid matrix upon exposure to metabolically noxious stimuli, or a variable combination of both processes. Epigenetic alterations have been shown to participate in this complex environment, through mechanisms including DNA methylation, non-coding RNAs, histone modifications, and chromatin changes. Despite such importance, existing reviews fail to provide a comprehensive view of all relevant reports addressing epigenetic processes in VC, and cross-talk between different epigenetic machineries is rarely examined. We conducted a systematic review based on PUBMED and MEDLINE databases up to 30 September 2019, to identify clinical, translational, and experimental reports addressing epigenetic processes in VC; we retrieved 66 original studies, among which 60.6% looked into the pathogenic role of non-coding RNA, followed by DNA methylation (12.1%), histone modification (9.1%), and chromatin changes (4.5%). Nine (13.6%) reports examined the discrepancy of epigenetic signatures between subjects or tissues with and without VC, supporting their applicability as biomarkers. Assisted by bioinformatic analyses blending in each epigenetic component, we discovered prominent interactions between microRNAs, DNA methylation, and histone modification regarding potential influences on VC risk.